Ethno-Ornithological Study of Birds Based on Local Wisdom in Plered Chicken Market Cirebon Regency as Biology Teaching Material - Samrotul Qulub; Diana Hernawati; Diki Muhamad Chaidir (Journal of Tropical Ethnobiology, 2023)
Birds are one of the most admired animals in almost all circles of society because of their beautiful visuals and sounds. However, many people need to learn the names of the various bird species that are abundant in Indonesia; they need to understand their conservation status, their role in life, and their relation to local wisdom that exists in society. Therefore, this study aims to describe the study of bird ethno-ornithology and its relation to the wisdom of local people around the Powered Chicken Market area, Cirebon Regency. This research method uses a case study type qualitative research method. The subjects in this study were bird traders at the Plered Chicken Market, Cirebon Regency and the surrounding community, who were selected by purposive sampling. The results showed that 568 individual birds could be identified at the Plered Chicken Market consisting of 65 species with 15 sub-species originating from 4 species and seven different orders. In addition, there are 14 types of bird utilization from 33 species related to the local wisdom of the people there. Likewise, the Use Value (U.V.) and Relative Frequency of Citation (R.F.C.) values range from 0.13-1.00, while the Fidelity Level (F.L.) value is 100%. The data obtained in this study were packaged as a flipbook-type digital book for learning material in biology learning.